Effect of anions on the self-assembly of two Cd–organic frameworks: syntheses, structural diversity and photoluminescence properties. Issue 3 (18th November 2014) - Xue, Zhenzhen; Sheng, Tianlu; Wen, Yuehong; Wang, Yong; Hu, Shengmin; Fu, Ruibiao; Wu, Xintao
Abstract : The assembly of a rigid tripodal ligand with two different Cd(ii ) salts produced two diverse metal–organic frameworks. Abstract : By employing a rigid tripodal ligand 1, 3, 5-tris(1-imidazolyl)benzene (tib) to assemble with two different Cd(ii ) salts, we have obtained two distinct cationic metal–organic frameworks, [Cd(tib)2 ·2NO3 ·4DMF] n (1 ) and [Cd(tib)2 ·2ClO4 ·4DMF] n (2 ) (DMF = N, N -dimethylformamide). The compounds were structurally characterized by single-crystal X-ray diffraction analyses and further characterized by infrared spectra (IR), elemental analyses, powder X-ray diffraction (PXRD), and thermogravimetric analyses (TGA). Both compounds1 and2 are constructed based on 2D square lattice (sql ) nets, through ligand-to-axial (L–A), pillared by triangular tib ligands, resulting in two diverse 3D pillar-layered architectures. Compound1 features a cationic framework with a (3, 6)-connectedrtl topology and has rhomboid channels; while for2, the 2D layers repeat in an ⋯ABAB⋯ staggered stacking mode pillared by tib ligands, resulting in a different cationic framework from1 with apyr net. The results demonstrate that counterions NO3 − and ClO4 − play an important role in the fabrication of structures of1 and2 . Furthermore, the photoluminescence of compounds1 and2 have been investigated in the solid state at ambient temperature.